Observational Insight Into the Subsurface Anomalies of Marine Heatwaves - Elzahaby, Youstina; Schaeffer, Amandine (Frontiers in Marine Science, 2019)
Marine heatwaves (MHWs) are extreme ocean warming events that can have devastating impacts, from biological mortalities to irreversible redistributions within the ocean ecosystem. MHWs are an added concern because they are expected to increase in frequency and duration. To date, our understanding of these extreme ocean temperature events is mainly limited to the surface layers, despite some of the consequences they are known to have on the deep marine environment. In this paper, using data from sea surface temperature (SST) and in situ observations from Argo floats, we investigate the anomalous water characteristics during MHWs down to 2000 m in the western Tasman Sea which is located off the east coast of Australia. Focusing on their vertical extensions, characteristics and potential drivers, we break MHWs down into three categories (1) shallow [0 – 150 m], (2) intermediate [150 – 800 m], and (3) deep events [> 800 m]. Only shallow events show a relationship between surface temperature anomalies and depth extent, in agreement with a likely surface origin in response to anomalous air-sea fluxes. By contrast, deep events have greater and deeper maximum temperature anomalies than their surface signal (mean of almost 3.4oC at 165 m depth) and are more frequent than expected (>45%), dominating MHWs in winter. They predominantly occur within warm core eddies, which are deep mesoscale anticyclonic structures carrying warm water-mass from the East Australian Current. This study highlights the importance of MHWs down to 2000 m and the influence of oceanographic circulation on their characteristics. Consequently, we recommend a complementary analysis of sea level anomalies and SST be conducted to improve the prediction of MHW characteristics and impacts, both physical and biological.